Alkali-metal Fluoridooxidovanadates(V) and their Complexes with XeF2 and HF - Lozinšek, Matic (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Complexes [Mn+(XeF2)p(AFx−)n] in which metal ion is coordinated by XeF2 ligands represent an important, diverse, and structurally rich family of noble-gas compounds. The most numerous are XeF2 coordination complexes of divalent metal cations, followed by complexes of lanthanide ions. The least represented are monovalent cations, where altogether only three structurally characterized complexes of Ag+ and Li+ have been reported. Anions are limited to weakly coordinating hexafluorido species, such as AsF6−, SbF6−, and RuF6−. Vanadium oxytrifluoride, VOF3, is a Lewis acid and with metal fluorides forms a variety of fluoridooxidovanadate(V) salts. In this work, alkali metal fluorides were reacted with VOF3 in anhydrous HF and the following compounds have been isolated and structurally characterized by single-crystal X-ray diffraction and Raman spectroscopy: Li2V2O2F8 and Na2V2O2F8 with dimeric anions; KVOF4 and KV2O2F7 with chain anions; and complexes with HF ligand [Na(HF)VOF4] and [K9(HF)2V9O9F36]. Moreover, crystallization of solutions of XeF2 and Li2V2O2F8 has resulted in the formation of [Li2(XeF2)V2O2F8], a rare example of XeF2 ligation to lithium. Similarly, when Na2V2O2F8 was employed, a complex [Na2(XeF2)V2O2F8] formed, which is the first example of XeF2 coordination to sodium ion. In both coordination compounds the XeF2 ligand exhibits M+–FXeF–M+ bridging coordination mode.